Improvement of strength and ductility synergy in a room-temperature stretch-formable Mg-Al-Mn alloy sheet by twin-roll casting and low-temperature annealing - T. Nakata; C. Xu; K. Kaibe; Y. Yoshida; K. Yoshida; S. Kamado (Journal of Magnesium and Alloys, 2022)
Strength and ductility synergy in an Mg-3mass%Al-Mn (AM30) alloy sheet was successfully improved via twin-roll casting and annealing at low-temperature. An AM30 alloy sheet produced by twin-roll casting, homogenization, hot-rolling, and subsequent annealing at 170 °C for 64 h exhibits a good 0.2% proof stress of 170 MPa and a large elongation to failure of 33.1% along the rolling direction. The sheet also shows in-plane isotropic tensile properties, and the 0.2% proof stress and elongation to failure along the transverse direction are 176 MPa and 35.5%, respectively. Though the sheet produced by direct-chill casting also shows moderate strengths if the annealing condition is same, the direct-chill casting leads to the deteriorated elongation to failure of 23.9% and 30.0% for the rolling and transverse directions, respectively. As well as such excellent tensile properties, a high room-temperature stretch formability with an Index Erichsen value of 8.3 mm could be obtained in the twin-roll cast sheet annealed at 170 °C for 64 h. The annealing at a higher temperature further improves the stretch formability; however, this results in the decrease of the tensile properties. Microstructure characterization reveals that the excellent combination of strengths, ductility, and stretch formability in the twin-roll cast sheet annealed at the low-temperature annealing is mainly attributed to the uniform recrystallized microstructure, fine grain size, and circular distribution of (0001) poles away from the normal direction of the sheet.